Coupling Seq-BSA and RNA-Seq Analyses Reveal the Molecular Pathway and Genes Associated with Heading Type in Chinese Cabbage - Gu, AiXia; Meng, Chuan; Chen, YueQi; Wei, Lai; Dong, Hui; Lu, Yin; Wang, YanHua; Chen, XuePing; Zhao, JianJun; Shen, ShuXing (Frontiers in Genetics, 2017)
In Chinese cabbage, the pattern formation of head top is a key agricultural trait of significant economic importance. Using a natural microspore-derived doubled haploid plant, we generated self-crossed progeny with overlapping or outward curling head morphotypes. Sequencing-based bulked segregant analysis (Seq-BSA) revealed a candidate region of 0.52 Mb (A06: 1824886 bp 2347097 bp) containing genes enriched for plant hormone signal transduction. RNA-Seq analysis supported the hormone pathway enrichment leading to the identification of two key candidate genes, BrGH3.12 and BrABF1. Expression of the former varied significantly in the apical portion of the leaf, consistent with the morphological differences between overlapping and outward curling type leaves. Expression of BrABF1 in the top, middle and basalsegments of the leaves was also significantly different between the two types. The two morphotypes contained different concentrations of IAA in the apical portion of their leaves while levels of ABA differed significantly between plant types in the top, middle, and basal leaf segments. Results from Seq-BSA, RNA-Seq and metabolite analyses all support a role for IAA and ABA in leaf head pattern formation at top region. These findings increase our understanding of the molecular basis for pattern formation of head top in Chinese cabbage and will contribute to future work developing more desirable leaf head patterns at top region.